Dampak Undang-Undang Nomor 23 Tahun 2014 Terhadap Peraturan Daerah di Kabupaten Bintan Tahun 2015 (Studi Peralihan Kewenangan Dibidang Kelautan dan Pertambangan) - Oksep Adhayanto; Yudhanto Satyagraha Adiputra (Jurnal Selat, 2015)
The complex policy on authority management between central and local government has appeared to be hot issue from each periods of the constitution implementation on the local governance. With the enactment of the newly issued Local Governance Law Number 23 Year 2014, has indirectly influenced legal products on which previously effective whether to district or head district law. Problem of this research is how authority management between central, provincial and district/municipal government is answered based on the Law Number 23 Year 2014 and the impacts on authority transformation in terms of ocean and mining affair. Basically, this research theoritically attempts to apply several approaches by integrating between more macro and micro systemic study, although not entirely practised. Law Number 23 Year 2014 implies a more de-constructing rather than reconstructing relationship between central and local government, by reducing authority of head district/city mayor in the development. Decentralization intrument has turned resources management of which previously held on the hand of district/city authority presently taken over by the provincial level of government, for instance : mining license shift for class C mined products and the sea territorial limit. Thus, the 2014 Local Governance Law makes necessary to cause juridical adjustment for the local legal products mainly related to certain authorities which are transferred from the provincial to district or regency level. Keywords: District Regulation, Bintan Goverment, Authority